Towards a fiscal union? On the acceptability of a fiscal transfer system in the eurozone - Shafik Hebous; Alfons J. Weichenrieder (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
There is a large, but yet growing debate about the need to complement the European monetary union with a stronger fiscal union. This paper reviews the potential trade-offs between effectiveness, moral hazard problems, and permanent redistribution. In particular, we contribute to the question of how member states may be willing to enter into a stronger fiscal union if the evolution of this union may imply large redistribution under incomplete contracting. We discuss clawback mechanisms that have been suggested in the literature, but conclude that clawbacks are undesirable, as they would essentially destroy the insurance value of a fiscal union. Instead, we propose that a clearly defined exit option as a guarantee against involuntary redistribution can make entry into a stronger fiscal union less risky and hence more attractive for member states.
urn:nbn:de:hebis:30:3-390617
Keywords: H1; H7; 330; EMU; Eurozone; European unemployment insurance; fiscal transfers